2018
DOI: 10.1089/jpm.2017.0431
|View full text |Cite
|
Sign up to set email alerts
|

A National Palliative Care Strategy for Canada

R. Sean Morrison

Abstract: Objective: To identify barrier to achieving universal access to high quality palliative care in Canada, review published national strategies and frameworks to promote palliative care, examine key aspects that have been linked to successful outcomes, and make recommendations for Canada. Background: In 2014, the World Health Organization called on members to develop and implement policies to ensure palliative care is integrated into national health services. Methods: Rapid review supplemented by the author's per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 11 publications
(16 reference statements)
2
51
0
Order By: Relevance
“…This result is consistent with the Institute of Medicine in the report of Dying in America: Improving Quality and Honoring Individual Preferences Near the End of Life that various socio-cultural, economic, and health system factors hinder the quality of end-of-life care in the United States [20]. Owing to its inherent complexity, the effects of merely institutional policies and professional societies on improving the provision of palliative and end-of-life care are insignificant [19,21]. Collaboration across organizations and care sectors is imperative to ensure equitable access to quality palliative and end-of-life care and consistency in care practices [18].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is consistent with the Institute of Medicine in the report of Dying in America: Improving Quality and Honoring Individual Preferences Near the End of Life that various socio-cultural, economic, and health system factors hinder the quality of end-of-life care in the United States [20]. Owing to its inherent complexity, the effects of merely institutional policies and professional societies on improving the provision of palliative and end-of-life care are insignificant [19,21]. Collaboration across organizations and care sectors is imperative to ensure equitable access to quality palliative and end-of-life care and consistency in care practices [18].…”
Section: Discussionsupporting
confidence: 86%
“…The Irish experience suggested that the support of policymakers is crucial for maintaining a substantial government budget for service development to widen access [18]. After reviewing the national strategies and frameworks related to palliative care of four top-ranked countries, Morrison (2018) identified the following keys to success: involving policy makers in strategy planning to overcome challenges in the infrastructure, implementing a standardized monitoring system to uphold quality evidence-based care, and maintaining an ongoing government investment to ensure sustainability [19]. Therefore, the overarching theme is to formulate a government-led policy framework that demonstrates government leadership in guiding service development.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, quality of care may be reasonably equitable among rich and poor, thereby mitigating feelings of frustration among lower-income caregivers. Second, palliative care services are more available to lower-income patients in North America and Europe [24][25]. The burden of responding to emergent symptoms is often reduced with the aid of medical management directed towards improving QOL.…”
Section: Goodmentioning
confidence: 99%
“…Most were married and many had young children -some of them had their eldest child just as old as 6 years and youngest merely 1 year, indicating increased psychological and social needs. Parenthood is one of the major concerns when diagnosed with an advanced illness [56], however, the needs speci c to dying patients and their dependent children are not well met even in the developed countries with comprehensive PC [57][58][59].…”
Section: Discussionmentioning
confidence: 99%